Your Eyes Do Not Lie! Dissecting Humor Effects in Health Messages Using Eye Tracker Technology - Brigaud, Emmanuelle; Lafont, Alex; Blanc, Nathalie (Frontiers in Public Health, 2021)
In the past decade, humor in scientific research has become more and more popular providing an increase of data identifying the context in which humor is a promising communication strategy in preventive health messages. To avoid the limits of declarative responses usually recorded in past studies, eye tracker technology offers the possibility to assess and dissect the effects of humor on visual attention. In this brief report, we first attempt to extend the results of previous studies by recording eye movements while participants were exposed to humorous and nonhumorous print health ads dealing with tobacco and alcohol consumption. A secondary purpose is specifically to test the visual attention French women devoted to humorous tobacco preventive ads, the worrying results of recent studies urging to find a way to improve tobacco preventive campaigns. Based on three complementary eye-tracking measures (i.e., total dwell time, fixation count, and revisits), the results showed that humorous health messages were scanned longer and more frequently and revisited more often compared to nonhumorous ones. In addition, humor appeared to reduce smokers' avoidance of preventive tobacco messages. The different pattern of visual exploration confirms that humor is a good strategy to grab attention even of individuals who are involved in the health topic addressed. In short, this paper argues for introducing lightness into a very serious subject, health communication, based on the analysis of eye movement evidence.